Kedudukan Ahli Waris Anak Laki-Laki Bungsu yang Sudah dan Belum Mandiri Terhadap Harta Bersama - Jhosua Kenjubel Pandapotan Sihombing; Widodo Ramadhana (CV Rewang Rencang, 2024)
The existence of Batak customary inheritance law is influenced by the paternal lineage (patrilineal) so that the heirs fall only to the sons. In Batak customary inheritance law, there is also a special privilege given to the youngest son, namely getting inheritance rights to the house left by his parents, in Batak terms known as jabu parsaktian. In the Batak Toba kinship system, the right to succeed is directly realized through the son, because he is the natural executor of the continuity of descent from the father's line, while women do not have certain rights in the Batak Toba customary kinship system. The objectives to be achieved in this writing are to obtain data and information on inheritance rights to the youngest son over a house inherited from his parents in the Batak Toba community, to reveal the legal consequences arising from the distribution of inheritance rights of the youngest son over a house inherited from his parents, to reveal the efforts made by Mangaraja Adat in resolving inheritance rights disputes over houses inherited from their parents against the youngest son among the Batak Toba community. This type of research uses normative and empirical juridical legal research that examines law as a system of normative structures. The source of research data is secondary data. The data collection technique in this study uses literature studies such as laws and regulations, scientific journals, law books related to cooperation and agency agreement laws. The research data collection tools are document studies and interview guidelines. The analysis of this research data was carried out qualitatively. The method of drawing conclusions used is the deductive method.